Evaluation of Temperature Stress Under Different Hydroponic Systems on Growth and Saponin Content of Talinum paniculatum Gaertn. Cuttings - Yachya, Arif; Kristanti, Alfinda Novi; Manuhara, Yosephine Sri Wulan (Journal of Tropical Biodiversity and Biotechnology, 2024)
Increases in the temperature of nutrient solutions have restricted the use of hydroponic cultivation in the tropics, predominantly due to plant stress. This study aimed to evaluate the effects of temperature stress under different hydroponic systems on the growth and saponin content of Talinum paniculatum cuttings. Three hydroponic systems, i.e., deep flow technique (DFT), nutrient film technique (NFT), and aeroponic, were tested. The temperature of the nutrient solution was set for each system, i.e., under ambient temperature (UAT) and with controlled temperature (WCT) at 26° C. The cultivation period was 60 days. The result showed peroxidation activity and proline accumulation for the adventitious roots of T. paniculatum cuttings with UAT and WCT, alongside various levels of plasma membrane damage. Levels of Malondialdehyde (MDA) and proline were analyzed by spectrophotometer. Membrane damage was analyzed with Evans blue dye. The results indicated that the levels of MDA and proline accumulation under the three hydroponic systems were higher for the WCT than for the UAT treatment. In contrast, vegetative growth was higher in UAT than in WCT. The saponin content of the adventitious root correlated with the MDA level. Saponin production was triggered by oxidative stress during cultivation, while the adventitious roots had a higher saponin content in all three hydroponic systems with the WCT treatment compared to the UAT treatment. Among the systems, aeroponic was superior for biomass and saponin. Root growth was promoted in the nutrient solution under ambient temperature whereas the production of saponins was stimulated under the controlled temperature. In the aeroponic system, root biomass values of 1.17 and 0.478 g dry weight were obtained under ambient and controlled temperatures, respectively. The total saponin contents differed slightly, namely 189.83 and 195.61 mg/g, respectively.